2017
DOI: 10.1002/maco.201709924
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of atmospheric corrosion near the coastal areas of Arabian Sea

Abstract: Atmospheric corrosion near the coastal areas of Karachi is a subject of great interest where seasonal variation of north Arabian Sea, high onshore activities, high levels of atmospheric pollutants, high humidity, and low temperature range affects the service life of structural materials. Mild steel test coupons were exposed at the two atmospheric corrosion stations located in National Institute of Oceanography (NIO) and Karachi Port Trust (KPT) along the coastal line of Karachi, Pakistan for a period of 12 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…The present study showed that the value of n is higher than 0.5 for both test stations. This is indicating that the nature of corrosion product was non‐protective so mixed diffusion and charge transfer control happened …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study showed that the value of n is higher than 0.5 for both test stations. This is indicating that the nature of corrosion product was non‐protective so mixed diffusion and charge transfer control happened …”
Section: Resultsmentioning
confidence: 99%
“…The concentration of chloride was moderate and falls in the S 2 category even though both test stations were marine. This may be due to the calm sea and vegetation along the shoreline which inhibits the air to carry the airborne salts from the sea . The concentration of sulfur dioxide was very high and fall in highest category P 3 which may be due to the emission activities of heavy cargoes and dumping of coal on the shore …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[6,7] This study is in continuation of author's previously reported efforts to classify the corrosivity category of prevailing atmospheric conditions in Karachi, Pakistan. [6,8] The main purpose of this study was to classify the corrosivity category of the atmosphere of the two sites using ISO 9223 norm. The sites were located at National Institute of Oceanography (NIO) and Karachi Port Trust (KPT) along the southeastern coastal route of China-Pakistan Economic Corridor (CPEC) project in Karachi, Pakistan.…”
Section: Introductionmentioning
confidence: 99%